Data Mining Clustering Korban Kejahatan Pelecehan Seksual dengan Kekerasan Berdasarkan Provinsi Menggunakan Metode AHC - Sundari, Mitha Amelia; Pane, Rahmadhani; Rohani, Rohani (Forum Kerjasama Pendidikan Tinggi, 2023)
Sexual harassment is one of the most common crimes in Indonesia recently. Acts of sexual harassment can occur in everyday life regardless of time, whether at work, on the street, or at home. Women are often the victims of sexual harassment, although men can experience the same. Perpetrators of sexual harassment can come from people we don't know, people who have hatred, even people we care about. Lack of religious and moral education, and technological developments that allow easy access to pornographic content are contributing factors to sexual harassment. To overcome this problem, fast action is needed in places where sexual harassment often occurs through socialization so that people are more vigilant when they are in these places. Apart from that, it is necessary to improve security in the area and provide consultation places such as psychologists. To identify places that are prone to sexual harassment in Indonesia, a data mining method is applied by utilizing previous data. The clustering method used is AHC using the complete linkage mode (longest distance) between the initial clusters. The final results of this research involve a manual process and the appropriate RapidMiner application, so that new clusters can be formed using RapidMiner. There are 5 provinces included in cluster 0, then there are 17 provinces in cluster 1, and 12 provinces in cluster 2